Influence of bottom environment conditions and hydrographic variability on spatiotemporal trends of macrofaunal amphipods on the Yucatan continental shelf. (15th July 2020) - Paz-Ríos, Carlos E.; Pech, Daniel; Mariño-Tapia, Ismael; Simões, Nuno
Abstract: Amphipod species collected during three oceanographic campaigns (2010–2012) were analyzed to describe their spatiotemporal community distribution trends and their relationships with bottom water and sediment variables. The results show that the species richness (117 spp.) did not reach its maximum value according to the species accumulation curve (up to 187 spp.). Multivariate analyses and constrained ordinations techniques detected three main amphipod assemblages along the longitudinal gradient (i.e., Western Caribbean, Mid-Yucatan, and West-Yucatan) and during two temporal hydrographic scenarios (i.e., upwelling in 2010–2011 and non-upwelling in 2012). In 2010–2011, low values in species richness and abundance from the Western Caribbean and eastern Mid-Yucatan assemblages were associated with relatively low bottom-water temperatures from the upwelling systems. In 2012, the absence of upwelling and the occurrence of a warm-core anticyclonic eddy seemed to cause an increase in species richness and abundance in the three assemblages. The hydrographic variability and sediment characteristics are suggested as the major environmental drivers that shapes the soft-bottom amphipod community structure and diversity in the Yucatan continental shelf. Highlights: Three species assemblages were identified along the longitudinal gradient. Depth gradient influence the species richness, abundance, and species composition. The upwelling systems influence the temporal variability of the species assemblages. Hydrographic and sedimentary variability induces major changes in the distribution and diversity of amphipods.